PENGARUH LATIHAN PASSING SEGI EMPAT TERHADAP TEKNIK DASAR PASSING SISWA PUTRA DI SEKOLAH SEPAK BOLA KSATRIA SOLO USIA 10-12 TAHUN - Muhammad Diaz Priambodo; Karlina Dwijayanti; Widha Srianto (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2023)
This study aims to determine the effect of rectangular passing practice on the ability of basic passing techniques of athletes at the Solo Knights Soccer School aged 10-12 years. The type of research used in this research is to use the design